2018
DOI: 10.5812/zjrms.14349
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aerobic and Anaerobic Exercises on the Level of Depression, Anxiety, Stress and Happiness of Non-Athlete Male

Abstract: Background and Objectives: Exercises bring about health. Therefore, knowing what kind of exercise is more effective in individuals' spirituals health indices is important. Thus, the present study aims at comparing the impact of aerobic and anaerobic exercises on the level of depression, anxiety, stress, and happiness of nonathletic male students. Methods: In this clinical trial study, sample included the nonathletic male students of Zahedan Azad University in 2014. 90 students were selected through convenience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Furthermore, Kianian et al . [ 41 ] did not find any significant differences in depression symptoms or happiness levels between aerobic and nonaerobic physical activity in nonathletic men. Differences in samples, duration of the course, and measurement tools could explain the inconsistencies with the current research.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, Kianian et al . [ 41 ] did not find any significant differences in depression symptoms or happiness levels between aerobic and nonaerobic physical activity in nonathletic men. Differences in samples, duration of the course, and measurement tools could explain the inconsistencies with the current research.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies thus suggest that aerobic exercise is superior to anaerobic exercise in reducing depressive symptoms, which is similar to our results. Kianian et al reported that in men, all kinds of exercise show reducing effects on depressive symptoms, but that anaerobic exercise showed a larger effect than aerobic exercise 29 . One possible explanation for this difference is that decreased muscle mass is significantly related to depressive symptoms, but only in men, which may explain the difference in the effect of anaerobic exercise between men and women 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic individuals can participate in these activities for extended durations [30]. It's recommended that they exercise 34 times per week, beginning with low intensity [31]. The Chronic Disease Management Program (PROLANIS) is implemented by BPJS.…”
Section: Introductionmentioning
confidence: 99%